Feasibility, reproducibility, and clinical implications of the fully automated assessment for global longitudinal strain. (25th November 2020) - Kawakami, H; Wright, L; Nolan, M; Potter, E.L; Yang, H; Marwick, T.H
Abstract: Background: Despite of evidence on its usefulness, measurement of global longitudinal strain (GLS) has not been widely accepted as a clinical routine because it requires proficiency and is time-consuming. Automated assessment of GLS may be a solution to these barriers. This study sought to investigate the feasibility, reproducibility, and predictive value of automated strain analysis compared with semi-automated and manual assessment for global longitudinal strain. Methods: In this validation study, different methods for the assessment of GLS were applied to echocardiograms of 561 asymptomatic people (age 71±5 years) with heart failure (HF) risk factors, recruited from the community. All patients were followed up for new-onset of HF and cardiovascular death. Measurement of GLS was repeated using the same apical images on three different measurement packages as follows: (1) fully automated GLS (AutoStrain), (2) semi-automated GLS (automated, corrected by a trained investigator), and (3) manual GLS (standard manual assessment by a trained investigator). We defined abnormal GLS for discrimination of LV systolic dysfunction using the cut-off of GLS =18% (absolute value). Results: AutoStrain measurements were feasible in 99.5% of patients. Calculation time for automated (0.5±0.1 min/patient) and semi-automated assessment (2.7±0.6 min/patient) were significantly shorter than that for manual assessment (4.5±1.6 min/patient) (both p<0.001), and the automated assessment showed excellent reproducibility. There was considerable discordance between automated and semi-automated/manual GLS (Figure 1), but normal systolic function was reliable identified. The prediction of cardiovascular events was reliable with automated, semi-automated and manual GLS (Figure 2). Conclusion: A novel fully automated assessment for GLS is a feasible, rapid, reproducible and clinically applicable means of assessing LV function, and measurements in the normal range predict a favorable outcome. Funding Acknowledgement: Type of funding source: None